Lichen: Comparative Study between Campus Area and Forest Sekipan Karanganyar Central Java - Roziaty, Efri; Furi, Ade Ratna (Universitas Muhammadiyah Surakarta, 2017)
Lichens are organism usually found on tree trunk and rocks. They are also very sensitive to pollutions. Meanwhile, the rapid increase in the use of motor vehicles has a huge impact on the emergence of pollution in most of environments. In fact, the increasing quantity of emission from the transportation sector, especially vehicles on the roads, has resulted high level of air pollution that influences the morphology of lichens. The aim of the research was to identify lichens growing naturally in the campus area and the natural habitat of the Sekipan forest. It was done by observing the population of lichens in two different stations. The study site was divided into two stations, namely campus area and the Sekipan forest. The research employed exploration method. The 1st station was the campus area and the 2nd station was the Sekipan forest. The parameters were the morphology and the colony of lichens. Species richness was revealed in which the diversity of lichens in Sekipan forest was higher in compared with those in the campus area. The results of the survey demonstrated the different species of lichen in campus area (Station 1) and Sekipan forest in Karanganyar, Central Java. Basically, lichens in the campus area are less in species diversity, but they have species richness in forest.